O homem levanta o mundo, a mulher sustenta o lar: A literatura doutrinária espírita contemporânea em perspectiva de gênero. - Bradbury, Roger (2015)
The results of the literature search corroborate what in religious practice I had already noted, the existence of certain intentional syncretism of apprehension and religious content review, in other words, the matrix Judeo-Christian worldviews impregnated with values and role models that marked the new Spiritualism gender representations, still in France, and later in Brazil. It was found that both in literature and in the spiritist ethos has always been an oscillation between a sexual division of more traditional androcentric with the overvaluation of women as mothers, and men work as providers - and as a consequence the limitation on skills development occurs and competencies of both sexes in the various social institutions (family, work, etc.), including the spiritist institutions on the one hand, and; On the other hand, an alleged defense posture of the progressive liberation (emancipation) of womens rights. This research aimed to analyze the representations of gender in literary-doctrinal productions of contemporary Brazilian Spiritism, from a survey of the historical context that would have influenced the development of the spirit gender representations from a stage prior to the institutionalization of Spiritism, in France and in Brazil, to the present day and how such representations of gender structure the internal organization of Spiritualism, regarding the sexual division of labor. In addition to literature search was performed analysis of the Spiritisms doctrinal literature.